KESANTUNAN BERBAHASA DALAM KOMENTAR CAPTION INSTAGRAM - Hartini, Henny Isnaini; Faizah AR, Hasnah; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study, entitled Language Politeness in the Comment Caption Instagram. The purpose of this study were described the caption comment in instagram that is accordance with the principle of language politeness. The method used is a descriptive method that illustrates the quantitative data. Furthermore, the results of this study found 101 speeches that fit the principle of politeness with a percentage of 100%. The principles of politeness in question include : (A)tact maxim of 8 speech or 7,9%; (B) generosity maxim of 4 speech or 3,9%; (C) approbation maxim of 25 speech or 24,8% (D) modesty maxim of 17 speech or 16,8% (E)agreement maxim of 26 speechor 25,8% and (F) sympath maxim of 21 speech or 20,8%.Key Words: Language Politeness,Comment Caption Instagram.